The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1155/2019/8079127
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cigarette Smoking on Retinal and Choroidal Thickness: A Systematic Review and Meta-Analysis

Abstract: Background Cigarette smoking has been regarded as a risk factor for the incidence of a wide variety of chronic illness; however, its effect on thickness of the retina or choroid is still unknown. Methods A consummate literature search was conducted in PubMed and Embase up to January, 2018. The quantitative synthesis was conducted by Stata 12.0. Results A total of 13 observational studies were included in this meta-analysis. In this meta-analysis of all available observational studies, no significant effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 35 publications
1
14
0
1
Order By: Relevance
“…Some have suggested that these differences were driven by thicker inner and outer nuclear layers in males 49 . While smoking has been identified as a modifiable risk factor for AMD 5 , 50 53 , we did not find any association between macular retinal thickness and smoking at baseline, which is also consistent with previous reports 54 , 55 . Once adjusted for age, baseline differences in retinal thickness among eyes with a grade 0 were driven by patients from the Chr1-prot-del group.…”
Section: Discussionsupporting
confidence: 93%
“…Some have suggested that these differences were driven by thicker inner and outer nuclear layers in males 49 . While smoking has been identified as a modifiable risk factor for AMD 5 , 50 53 , we did not find any association between macular retinal thickness and smoking at baseline, which is also consistent with previous reports 54 , 55 . Once adjusted for age, baseline differences in retinal thickness among eyes with a grade 0 were driven by patients from the Chr1-prot-del group.…”
Section: Discussionsupporting
confidence: 93%
“…A consistent trend was observed in each analysis; however, P -values were not consistently significant probably due to the large variation within groups. Previously, tobacco-associated retinal changes were also observed in otherwise healthy subjects ( Yang et al , 2019 ). However, the change was observed as thinning of retinal nerve fibre layer and ganglion cell layer.…”
Section: Discussionmentioning
confidence: 72%
“…Smoking was considered to be a possible factor that affects choroidal thickness. However, a meta-analysis showed that no significant effect of tobacco smoking on choroidal thickness change was detected (Yang et al, 2019 ). Furthermore, it was noted in this study that no significant difference exists in SFChT between smokers and nonsmokers.…”
Section: Discussionmentioning
confidence: 99%